Privacy in statistical databases UNESCO chair in data privacy, International conference, PSD 2012, Palermo, Italy, September 26-28, 2012. Proceedings - Tinnirello, Ilenia; Domingo-Ferrer, Josep (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the International Conference on Privacy in Statistical Databases, PSD 2012, held in Palermo, Italy, in September 2012 under the sponsorship of the UNESCO chair in Data Privacy. The 27 revised full papers presented were carefully reviewed and selected from 38 submissions. The papers are organized in topical sections on tabular data protection; microdata protection: methods and disclosure risk; microdata protection: case studies; spatial data protection; differential privacy; on-line databases and remote access; privacy-preserving protocols.